Expression of norA, norB and norC efflux pump genes mediating fluoroquinolones resistance in MRSA isolates - Asmaa B Hamady; Noha M Abd El-Fadeal; Samar Imbaby; Hassnaa MA Nassar; Mohamed Gamal Sakr; Yara E Marei (Journal of Infection in Developing Countries)
Introduction: Although fluoroquinolones are used to treat methicillin-resistant Staphylococcus aureus (MRSA)-induced infections, acquisition of antibiotic resistance by bacteria has impaired their clinical relevance. We aimed to evaluate the frequency of norA, norB, and norC efflux pump genes-mediating fluoroquinolones resistance and measure their expression levels in MRSA isolates.